Effect of certain botanicals on biological activity of nuclear polyhedrosis virus of tobacco caterpillar (Spodoptera litura) - BASKARAN, R K; VENUGOPAL, M S; MAHADEVAN, N R (The Indian Journal of Agricultural Sciences, 2013)
Result of the laboratory experiment on the control of tobacco caterpillar (Spodoptera litura Fabricius) with its nuclear polyhedrosis virus alone at I X IDs POBsf/ml and in combination at 2 X 104 POBs/ml (LC50 of SI NPV) with 1% neem oil and neem-seed-kemel extract and 5% neem-cake-extract indicated that there was an increase in efficacy of nuclear polyhedrosis virus and the virus induced mortality was enhanced from 31.1 mean per cent mortality to 81.5, 81.5 and 57.6% respectively. Combination of nuclear polyhedrosis virus with Vitex negundo Linn. 10% did not increase the efficacy of nuclear polyhedrosis virus appreciably, while Prosoplis juliflora DC. and Ipomoea carnea Jacq. had antagonistic effect with nuclear polyhedrosis virus. Nuclear polyhedrosis virus along with necm products reduced the leaf damage by larvae and LT50 of nuclear polyhedrosis virus. Suspending nuclear polyhedrosis virus in different concentrations (0.10-1 .00%) of neem oil and neem-seed-kemel-extract reduced the LC50 of nuclear polyhedrosis virus by 1.06 to 1.43 folds and 1.03 to 1.33 folds respectively.